القواعد الثلاثة في فكر عبد المقسط غزالي: دراسة تحليلية نقدية = The three principles of Abdul Moqsith Ghozali: an analytical and critical study - Ardiansyah, Rizky; Mat Jubri@Shamsuddin, Mustafa (Department of Fiqh and Usul, Academy of Islamic Studies, University of Malaya, 2023)
This article analyzes the three principles of Abdul Moqsith Ghozali discourse, namely “substance over form”, “the texts can be abrogated by “Maṣlaḥah”, and “the texts can be revised by the intellect of society”. In order to clarify this article, the researcher relied on the inductive approach to gather information related to the subject. The study employs a critical and analytical approach in analyzing the views adopted by Abdul Moqsith and discusses his opinions in the light of the recognized principles. The researcher has reached several results, including Abdul Moqsith avoiding the methods of the Uṣūliyīn in devising terms by disassembling them. He has three principles that have no controls and limits in their uses and applications. It appeared that the three principles are not new principles but are taken from weighted principles, and then derive and develop them.